Remote OSCE Experience: What First Year Pharmacy Students Liked, Learned, and Suggested for Future Implementations - Amanda Savage; Lana M. Minshew; Heidi N. Anksorus; Jacqueline E. McLaughlin (MDPI AG, 2021)
During the wake of the COVID-19 pandemic, many schools quickly transitioned their teaching and assessment strategies to online formats. In Spring 2020, a 3-station remote Objective Structured Clinical Examination (OSCE) was implemented for first-year pharmacy students. The day following the remote OSCEs students answered three open-text prompts about the remote OSCE experience: (1) "I liked...", (2) "I learned...", and (3) "I suggest...". Responses were open-coded and frequency counts were calculated to determine the most prevalent codes. Concept maps were created to visualize and explore connections between the codes. Out of 157 students, 156 students completed the reflection assignment, a 99.36% response rate. The three major themes in the Liked data were: Logistics (n = 65, 41.7%), Differences In-person Versus Remote (n = 59, 37.8%), and Skill Development (n = 43, 27.6%). The three major themes in the Learned data were: Technology (n = 66, 42.3%), Communication (n = 58, 37.2%), and Skill Development (n = 56, 35.9%). The three major themes in the Suggest data were: Logistics (n = 89, 57.1%), Technology (n = 31, 19.9%), and Continuation of Remote OSCE (n = 31, 19.9%). Overall, the remote OSCE experience was well-received, and students described it as applicable to their future pharmacy practice. Future work should explore the design, implementation, and outcomes of remote OSCEs.